Extracellular histones reduce survival and angiogenic responses of late outgrowth progenitor and mature endothelial cells. (4th February 2016) - Mena, H. A.; Carestia, A.; Scotti, L.; Parborell, F.; Schattner, M.; Negrotto, S.
Abstract : Essentials Extracellular histones are highly augmented in sites of neovessel formation, such as regeneration tissues. We studied histone effect on survival and angiogenic activity of mature and progenitor endothelial cells. Extracellular histones trigger apoptosis and pyroptosis and reduce angiogenesis in vivo and in vitro . Histone blockade can be useful as a therapeutic strategy to improve angiogenesis and tissue regeneration. Summary: Background: Extracellular histones are highly augmented in sites of neovessel formation, like regeneration tissues. Their cytotoxic effect has been studied in endothelial cells, although the mechanism involved and their action on endothelial colony‐forming cells (ECFCs) remain unknown. Objective: To study the effect of histones on ECFC survival and angiogenic functions and compare it with mature endothelial cells. Methods and Results: Nuclear morphology analysis showed that each human recombinant histone triggered both apoptotic‐like and necrotic‐like cell deaths in both mature and progenitor endothelial cells. While H1 and H2A exerted a weak toxicity, H2B, H3 and H4 were the most powerful. The percentage of apoptosis correlated with the percentage of ECFCs exhibiting caspase‐3 activation and was zeroed by the pan‐caspase inhibitor Z‐VAD‐FMK. Necrotic‐like cell death was also suppressed by this compound and the caspase‐1 inhibitor Ac‐YVAD‐CMK, indicating that histones triggered ECFC pyroptosis. All histones, at non‐cytotoxic concentrations, reduced migration and H2B, H3 and H4 induced cell cycle arrest and impaired tubulogenesis via p38 activation. Neutrophil‐derived histones exerted similar effects. In vivo blood vessel formation in the quail chorioallantoic membrane was also reduced by H2B, H3 and H4. Their cytotoxic and antiangiogenic effects were suppressed by unfractioned and low‐molecular‐weight heparins and the combination of TLR2 and TLR4 blocking antibodies. Conclusions: Histones trigger both apoptosis and pyroptosis of ECFCs and inhibit their angiogenic functions. Their cytotoxic and antiangiogenic effects are similar in mature endothelial cells and disappear after heparin addition or TLR2/TLR4 blockade, suggesting both as therapeutic strategies to improve tissue regeneration.